Expression of c-Fos in the rat retrosplenial cortex during instrumental re-learning of appetitive bar-pressing depends on the number of stages of previous training - Svarnik, Olga E.; Bulava, Alexandra I.; Alexandrov, Yury I. (Frontiers in Behavioral Neuroscience, 2013)
Learning is known to be accompanied by induction of c-Fos expression in cortical neurons. However, not all neurons are involved in this process. What the c-Fos expression pattern depends on is still unknown. In the present work we studied whether and to what degree previous animal experience about Task 1 influenced neuronal c-Fos expression in the retrosplenial cortex during acquisition of Task 2. Animals were progressively shaped across days to bar-press for food at the left side of the experimental chamber (Task 1). This appetitive bar-pressing behavior was shaped by nine stages ("9 stages" group), five stages ("5 stages" group) or one intermediate stage ("1 stage" group). After all animals acquired the first skill and practiced it for five days, the bar and feeder on the left, familiar side of the chamber were inactivated, and the animals were allowed to learn a similar instrumental task at the opposite side of the chamber using another pair of a bar and a feeder (Task 2). The highest number of c-Fos positive neurons was found in the retrosplenial cortex of "1 stage" animals as compared to the other groups. The number of c-Fos positive neurons in "5 stages" group animals was significantly lower than in "1 stage" animals and significantly higher than in "9 stages" animals. The number of c-Fos positive neurons in the cortex of "9 stages" animals was significantly higher than in home caged control animals. At the same time, there were no significant differences between groups in such behavioral variables as the number of entrees into the feeder or bar zones during Task 2 learning. Our results suggest that c-Fos expression in the retrosplenial cortex during Task 2 acquisition was influenced by the previous learning history.